Beyond individual cognitions: time for intervention science to focus on health context and audience - Chalabaev, Aïna; Cheval, Boris; Maltagliati, Silvio; Saoudi, Ilyes; Sniehotta, Falko F. (Journal of physical activity and health, 2023)
Intervention science faces a hazardous paradox: on the one hand, vulnerable populations (eg, patients, people from low socioeconomic background, older adults) are those for whom adoption of healthy behaviors is most urgent; on the other hand, behavior change models are less predictive, and interventions less successful, in these populations. This commentary presents 4 reasons that may explain this issue: (1) research mostly focuses on what causes behavior and how to change it, at the expense of investigating among whom and under what conditions models are valid; (2) models put an undue emphasis on individual cognitions; (3) most studies are not conducted on vulnerable populations; and (4) most researchers are from high-income countries. Several avenues are proposed to address this issue: (1) providing a central place to the context and audience in health behavior change modelization, through collaborations with researchers from other disciplines and countries, and with members of the targeted audience; (2) better reporting samples’ sociodemographic characteristics and increasing samples’ diversity; and (3) using more rigorous and innovative designs (eg, powered randomized controlled trials, N-of-1 trials, intensive longitudinal studies). In conclusion, it becomes urgent to change the way we do research: the social utility and credibility of intervention science depend on it.